Effects of Inorganic Phosphate on the Light Dependent Thylakoid Energization of Intact Spinach Chloroplasts - Heineke, Dieter (1989)
The light dependent energization of the thylakoid membrane was analyzed in isolated intact spinach (Spinacia oleracea L.) chloroplasts incubated with different concentrations of inorganic phosphate (Pi). Two independent methods were used: (a) the accumulation of [(14)C]5,5-dimethyl-2,4-oxazolidinedione and [(14)C] methylamine; (b) the energy dependent chlorophyll fluorescence quenching. The inhibition of CO(2) fixation by superoptimal medium Pi or by adding glyceraldehyde—an inhibitor of the Calvin cycle—leads to an increased energization of the thylakoid membrane; however, the membrane energization decreases when chloroplasts are inhibited by suboptimal Pi. This specific `low phosphate' effect could be partially reversed by adding oxaloacetate, which regenerates the electron acceptor NADP(+) and stimulates linear electron transport. The energization seen in low Pi is, however, always lower than in superoptimal Pi, even in the presence of oxaloacetate. Energization recovers in the presence of low amounts of N,N′-dicyclohexylcarbodiimide, which reacts with proton channels including the coupling factor 1 ATP synthase. N,N′-Dicyclohexylcarbodiimide has no effect on energization of chloroplasts in superoptimal Pi. These results suggest there is a specific `low phosphate' proton leak in the thylakoids, and its origin is discussed.